Chaining and Virtual Organization in a Slow Sociology Project: The Brown Ridge School District Health Needs Assessment Becomes the Central Susquehanna Affordable Care Act Project. (September 2015) - Milofsky, Carl; Green, Brandn
This article presents two case studies, linked together as chained projects, as examples of public sociology involving university/community partnerships. Research described here illustrates specific ways that applied sociology and public sociology can be put to work to address community problems. While the projects described here are an important focus, the article argues that they are primarily valuable in showing how a regional resource exchange network can be set up over a period of decades and how the presence of these partnerships creates the possibility for one project to chain into another. We describe this chaining as a resource exchange network and as a "virtual organization." Virtual organizations are intentionally created, possess internal logic, and contain a set of actors who carry out interdependent roles. Virtual organizations lack formal structure and require a minimum of organizational maintenance. The chaining method and the associated virtual organization help to bring university actors and resources to bear on helping to solve community problems.